Generalized Dicke model as an integrable dynamical system inverse to the nonlinear Schrödinger equation - Samuliak, R. V. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We prove that a dynamical system obtained by the space-time inversion of the nonlinear Schrödinger equation is equivalent to a generalized Dicke model. We study the complete Liouville integrability of the obtained dynamical system.